SIKAP KELUARGA DAN JARAK TEMPAT TINGGAL BERPERAN DALAM KETERLAMBATAN WAKTU KEDATANGAN PASIEN STROKE KE INSTALASI GAWAT DARURAT - Ali Hamzah; Tina Ristiani; Anah Sasmita; Zaenal Muttaqin; Sansri Dwidasmara; Yosep Rohyadi (Poltekkes Kemenkes Bandung, 2025)
Stroke remains a leading cause of disability and mortality, with a notably high prevalence in West Java Province in 2018, reaching 11.4 per 1,000 individuals surpassing the national average of 10.9 per 1,000. Prompt medical intervention within the first three hours after stroke onset commonly referred to as the golden period is critical for optimal outcomes. However, many patients continue to experience delayed hospital arrival. Two primary contributing factors are the lack of prompt response from family members and the considerable distance between the patient's residence and the hospital. This study aimed to examine the relationship between family responsiveness and residential distance with delayed hospital arrival among stroke patients. A correlational analytic approach was used with a cross-sectional study design. The sample included 50 participants, selected using purposive sampling. Data processed and analyzed by chi-square test. Findings revealed that 68% of respondents demonstrated low levels of family responsiveness and resided ≥10 kilometers from the hospital. These individuals were typically brought to the hospital more than three hours post-attack. Statistical analysis confirmed a significant relationship between both variables and the delay in hospital arrival (P=0.012). The results underscore the importance of enhancing family awareness and responsiveness through targeted education about the critical timing of stroke care. Additionally, hospitals should consider implementing hotline or early warning systems to facilitate faster response times and improve access to emergency services.